The effort of female characters to preserve national identity in the selected novels by contemporary Slovenian female writers - Kraner, Tina (Slavia Centralis, 2023)
In this article, I discuss the characteristics of female characters in four selected novels by contemporary Slovenian female writers, all published after 2000: Nedeljka Pirjevec’s Saga o kovčku (2003), Vilma Puričʼs Burjin čas (2009), Maruša Kreseʼs Da me je strah? (2012) and Tanja Tumaʼs Češnje, bele in rdeče (2015). As an introduction, I present the theoretical findings on identity, both national and ethnic, and analyse the works on that basis. The role of Slovenian literature in the formation of the national consciousness, the question of gender identity and the tradition of war prose in literature by Slovenian female writers are also highlighted. The selected war-themed novels present strong female characters who fight for preserving national identity in order to defeat the occupiers.